2019
DOI: 10.3390/en12132555
|View full text |Cite
|
Sign up to set email alerts
|

T2S2G: A Novel Two-Tier Secure Smart Grid Architecture to Protect Network Measurements

Abstract: False data injection (FDI) attacks are a major security threat to smart grid (SG) communication systems. In FDI attacks, the attacker has the ability of modifying the measurements transmitted by smart grid entities such as smart meters, buses, etc. Many solutions have been proposed to mitigate FDI attacks in the SG. However, most of these solutions rely on centralized state estimation (SE), which is computationally expensive. To engulf this problem in FDI attack detection and to improve security of SGs, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It is shown that more frequent data exchange increases obtained welfare. There are other implementations where more high-resolution data are required for proper operations' planning, such as re-synchronization of microgrids [34], protection coordination with high renewable energy penetration [35], [36], and filtering sound data from false data packets [37].…”
Section: V a L U E O F D A T A S T A N D A R D I Z A T I O Nmentioning
confidence: 99%
“…It is shown that more frequent data exchange increases obtained welfare. There are other implementations where more high-resolution data are required for proper operations' planning, such as re-synchronization of microgrids [34], protection coordination with high renewable energy penetration [35], [36], and filtering sound data from false data packets [37].…”
Section: V a L U E O F D A T A S T A N D A R D I Z A T I O Nmentioning
confidence: 99%
“…Hence, attacks on smart meter can impact on the Confidentiality, Integrity and Availability (CIA) triad of an energy systems demand side management. Therefore, the security issues have been highlighted as a major concern of today's smart grid smart meter communication and data management (Aziz et al, 2019;Ni & Paul, 2019;Anwar, Mahmood & Tari, 2017). Hence, it is necessary to build a powerful security framework for the smart grid system.…”
Section: Introductionmentioning
confidence: 99%
“…Awan et al highlight that industrialization increases the demand for renewable energy resources and decreases sustainability of greenhouse gas emissions [3]. With the emergence of environmental problems and the consumption of non-renewable energy, the application of renewable energy such as wind and solar energy is more and more important [4]. Shady et al highlight in [5] that the establishment of SGs is very important to improve the efficiency and security of energy supply.…”
Section: Introductionmentioning
confidence: 99%